1995
DOI: 10.2527/1995.732541x
|View full text |Cite
|
Sign up to set email alerts
|

An increase in serum lipids increases luteal lipid content and alters the disappearance rate of progesterone in cows

Abstract: To determine whether an increase in serum lipids alters the area occupied by lipid droplets in steroidogenic luteal cells and(or) clearance rates of progesterone from serum, pregnant beef heifers received control (n = 6) or treatment (n = 5) diets. To increase serum lipids, the treatment diet contained calcium soaps of fatty acids. Control and treatment diets were formulated to be isocaloric and isonitrogenous. Feeding of diets was initiated approximately 100 d before parturition and continued through the thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
68
5
14

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 13 publications
15
68
5
14
Order By: Relevance
“…Those authors concluded that the plasma concentrations of LNA (less than 8 µM) after the linseed oil infusions were not sufficient to inhibit the key enzymes responsible for P 4 metabolism (P450 2C and P450 3A) and thus, did not decrease hepatic clearance of P 4 . Hawkins et al (1995) reported increased serum concentrations of P 4 in pregnant heifers when calcium salts of FA were fed at 0.57 kg/heifer daily. Fouladi-Nashta et al (2007) only observed a tendency for greater P 4 concentrations when lactating dairy cows were fed 0.80 kg/d of calcium salts of FA compared with 0.20 kg/d.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those authors concluded that the plasma concentrations of LNA (less than 8 µM) after the linseed oil infusions were not sufficient to inhibit the key enzymes responsible for P 4 metabolism (P450 2C and P450 3A) and thus, did not decrease hepatic clearance of P 4 . Hawkins et al (1995) reported increased serum concentrations of P 4 in pregnant heifers when calcium salts of FA were fed at 0.57 kg/heifer daily. Fouladi-Nashta et al (2007) only observed a tendency for greater P 4 concentrations when lactating dairy cows were fed 0.80 kg/d of calcium salts of FA compared with 0.20 kg/d.…”
Section: Discussionmentioning
confidence: 99%
“…Adding calcium soaps of FA to the diet increased serum concentrations of P 4 in bovine females (Hightshoe et al, 1991;Hawkins et al, 1995). Greater concentrations of P 4 before and after breeding are associated with enhanced fertility (Folman et al, 1973) and embryonic survival (Mann et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that supplementation of cattle with PUFAs increased the plasma concentrations of steroid by stimulating ovarian production of steroid hormones through various mechanisms, including increased availability of lipoprotein-cholesterol (Hawkins et al, 1995;Lammoglia et al, 1996), modulation of prostaglandin synthesis (Knickerbocker et al, 1986), and the direct stimulation of ovarian steroidogenesis (Staples et al, 1998). In another study on cows, it was shown that diets enriched in n-6 PUFAs increased the secretion of progesterone by the granulosa cells (Wehrman et al, 1991).…”
Section: Nefasmentioning
confidence: 99%
“…In addition to helping meet energy demands, supplemental lipids influence reproductive performance in bovine females. Supplementing cows with dietary lipid increased concentrations of serum lipids [1,2], altered ovarian follicular development [2,3], and prostaglandin (PG) synthesis [4][5][6]. In late-pregnant ewes, diets high in linoleic acid increased plasma concentrations of arachidonic acid [7] and production of PG from endometrial tissue [7,8].…”
Section: Introductionmentioning
confidence: 99%